PERBEDAAN MODEL PEMBELAJARAN MIND MAPPING DAN KONVESIONAL TENTANG HASIL BELAJAR BIOLOGI KONSEP KEANEKARAGAMAN HAYATI PADA SISWA KELAS X SMA NEGERI WAEPUTIH KECAMATAN WAPLAU KABUPATEN BURU - Lenta N Simbolon; Ine Arini (Program Studi Pendidikan Biologi FKIP Unpatti, 2017)
Background: The success of the learning process requires the motivation in the students themselves to be able to encourage them to do activities in the learning activities. In the implementation, appropriate learning model is needed that can generate student motivation to learn. The use of the right teaching model is to use the Mind Mapping learning model. Method: The type of research used in this study is a quasi-experimental study or Quasi experiment. The design of this study is non-equivalent pretest-posttest consisting of mind mapping class and conventional class. The population in this study is all students of grade X SMA Negeri Waeputih, which consists of 3 classes of 72 students. The sample in this study were students of class X-1 and X-3 with each student 21 people. Sampling is done randomly. Result: The result of the research used the learning model of Mind Mapping and Conventional average student value in Mind Mapping class 100% higher than the average value of conventional class of 80%. Conclusion: There is a difference of students' learning outcomes proven on the result of t-test analysis where thitung 5.14> ttabel 1.01. Keywords: Mind Mapping Learning Model, Learning Outcomes, Biodiversity